Reduced immunomodulatory metabolite concentrations in peri-transplant fecal samples from heart allograft recipients - Dela Cruz, Mark; Lin, Huaiying; Han, Jiho; Adler, Emerald; Boissiere, Jaye; Khalid, Maryam; Sidebottom, Ashley; Sundararajan, Anitha; Lehmann, Christopher; Moran, Angelica; Odenwald, Matthew; Stutz, Matthew; et al. (Frontiers in Transplantation, 2023)
Background Emerging evidence is revealing the impact of the gut microbiome on hematopoietic and solid organ transplantation. Prior studies postulate that this influence is mediated by bioactive metabolites produced by gut-dwelling commensal bacteria. However, gut microbial metabolite production has not previously been measured among heart transplant (HT) recipients. Methods In order to investigate the potential influence of the gut microbiome and its metabolites on HT, we analyzed the composition and metabolite production of the fecal microbiome among 48 HT recipients at the time of HT. Results Compared to 20 healthy donors, HT recipients have significantly reduced alpha, i.e. within-sample, microbiota diversity, with significantly lower abundances of key anaerobic commensal bacteria and higher abundances of potentially pathogenic taxa that have been correlated with adverse outcomes in other forms of transplantation. HT recipients have a wide range of microbiota-derived fecal metabolite concentrations, with significantly reduced levels of immune modulatory metabolites such as short chain fatty acids and secondary bile acids compared to healthy donors. These differences were likely due to disease severity and prior antibiotic exposures but were not explained by other demographic or clinical factors. Conclusions Key potentially immune modulatory gut microbial metabolites are quantifiable and significantly reduced among HT recipients compared to healthy donors. Further study is needed to understand whether this wide range of gut microbial dysbiosis and metabolite alterations impact clinical outcomes and if they can be used as predictive biomarkers or manipulated to improve transplant outcomes.